Trends of Halal Industry Research: A Bibliometric Analysis - Ayu Safitri; Mukhamad Yazid Afandi (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT The halal industry provides great opportunities for the provision of goods and services, both domestically and internationally, in the future. The halal industry is one of the topics discussed in several scientific forums. The aim of this research was to discuss the development of research trends in the halal industry over a period of 27 years. This research used bibliometric analysis methods to examine in more depth scientific works and literature that discuss the halal industry in order to study the concept and its development from year to year. Data was collected through searching for articles indexed by Scopus with the acquisition of 960 documents related to the halal industry published between 1997-2023. Data were analyzed using VOSviewer software into three categories, namely network visualization, overlay visualization, and density visualization. The findings show that publications regarding the halal industry have increased significantly. Halal industry research trends based on the author show that Ali, M.H. is the most productive author. The development of halal industry research trends based on keywords shows that halal is the most frequently used keyword, followed by the keywords halal industry, halal tourism, halal food, and Malaysia. Malaysia is the country that has contributed the most to halal industry research. Keywords: Halal, Halal Industry, Bibliometric, Scopus   ABSTRAK Industri halal memberikan peluang besar bagi penyediaan barang dan jasa, baik domestik maupun internasional, di masa depan. Industri halal menjadi salah satu topik yang dibahas di beberapa forum ilmiah. Tujuan dari penelitian ini adalah untuk membahas perkembangan tren penelitian pada industri halal dalam kurun waktu 27 tahun. Menggunakan metode analisis bibliometrik untuk mengkaji lebih mendalam karya-karya ilmiah dan literatur tentang industri halal guna mempelajari konsep serta perkembangannya. Data dikumpulkan melalui pencarian artikel yang terindeks oleh Scopus dengan perolehan sebanyak 960 dokumen yang diterbitkan antara tahun 1997-2023. Data dianalisis dengan menggunakan software VOSviewer ke dalam tiga kategori yaitu network visualization, overlay visualization dan density visualization. Hasil penelitian menunjukkan bahwa publikasi mengenai industri halal mengalami peningkatan yang signifikan. Tren penelitian industri halal berdasarkan penulis menunjukkan bahwa Ali, M.H. merupakan penulis yang paling produktif. Perkembangan tren penelitian industri halal berdasarkan kata kunci menunjukkan bahwa halal merupakan kata kunci yang paling banyak digunakan, diikuti kata kunci halal industri, halal tourisme, halal food, dan Malaysia. Malaysia merupakan negara yang paling banyak berkontribusi dalam penelitian industri halal. Keywords: Halal, Industri Halal, Bibliometrik, Scopus